Conceptual model for talus slope development in Brattegg Valley (SW Spitsbergen) based on sedimentology of debris deposits in periglacial zone - Senderak, Krzysztof (Polish Polar Research, 2023)
The talus slopes occur in all climatic zones on the Earth. These forms are sensitive to climate fluctuations, therefore they may be indicators of changes in the environment and contain the record of the geomorphological events after the deglaciation period. Both in the past and nowadays, slopes in area of the High Arctic have been developing in the specific conditions of periglacial zone. This is caused by simultaneously occurring different processes of weathering and deposition. The article presents the methodological approach and the results of the sedimentological measurements and geomorphological studies of the eight talus cones located in SW Spitsbergen. The study was conducted in the non-glaciated valley near the Stanislaw Baranowski Polar Station in Spitsbergen. The aim of the investigation was to determine the modern mechanisms of material transport on talus slopes and their impact on relief of slope surface in the polar environment. The obtained results and literature data allowed to indicate four separate zones of talus slope environment and develop a conceptual model for talus slope development in the Brattegg Valley, SW Spitsbergen.